KOMUNIKASI POLITIK PARA ELIT DI ERA VIRTUAL CULTURE - Lilik Sumarni (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
A virtual world had been created to join the world of reality. Activities of political elites, especially in a political  setting,  with  the  efficacy  of  the  strategy  by  clicking  and  engineering  the  public  opinion  of discourses; war discourse by harnessing the power of media. Social media in a time vortex became a very  significant  machine  to  determine  our  lifestyles,  political  attitudes  in  addition  to  bring  online  a very lucrative business online, including politics. Mingling of political and economic interests became so  dominant  in  the  realm  of  the  media  industry.  The  presence  of  social  cyber  space  provided  a  new perspective  in  understanding  the  development  of  political  discourse.  In  this  virtual  world  era,  the current information relating to politics is easy to obtain and there had  been a fatality information that ended up being a mockery, entertainment and humor that no longer had a value, function and meaning, they  were mingled and distorted by the capitalist interests  who only promote business oriented alone regardless of content. The presence of social media became an implement of shaping the new culture included  culture  and  attitudes  of  political  elites,  mirror-imaging  and  political  marketing  that  had created  divisions  and  made  the  boxes  of  support  political  for  the  political  actors  with  political advertising strategy in the form of imaging. Accommodations of mass media for the image of politics were understood in the perspective of the economy, especially  in the law of supply and demand that became  the  logical  characteristic  and  market  regulation.  When  politic  become  a  commodity,  and ultimately the reality of elections can be capitalized, the media and the public image of political cyber regarded as legitimate and so natural, and everyone is free to create strategies to meet their interests.Keywords: Political Communication, Elites, Virtual Culture